2022
DOI: 10.1002/jat.4392
|View full text |Cite
|
Sign up to set email alerts
|

Particle surface functionalization affects mechanism of endocytosis and adverse effects of silver nanoparticles in mammalian kidney cells

Abstract: Silver nanoparticles (AgNPs) show a plethora of possible applications due to their antimicrobial properties. Different coatings of AgNPs are used in order to increase stability, availability, and activity. However, the question about the toxicity after prolonged exposure still remains. Here, we show that different surface coatings affect in vitro toxicity and internalization of AgNPs in porcine kidney (PK15) cells. AgNPs coated with cetyltrimethylammonium bromide (CTAB), poly(vinylpyrrolidone) (PVP), sodium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The toxicity of MPs was dependent on the activity of MPs at a biointerface and correlated with the number of internalized particles. 11 Provided that the increase of SSC intensity represented the uptake of particles in cells, 53 the concentration-dependent increase of SSC by secondary MPs suggested that phototransformation enhanced the cellular uptake of MPs, in contrast to the nearly unchanged SSC intensity for original EMPs (Figure 8a). Due to the close contact of MPs on the cell membrane, the positively charged MPs showed higher cytotoxicity than the negatively charged MPs, 54 which was opposite to the higher cytotoxicity caused by the carbonyl MPs in this study.…”
Section: Characterization Of Zno Nps and Mps Extracted Frommentioning
confidence: 99%
“…The toxicity of MPs was dependent on the activity of MPs at a biointerface and correlated with the number of internalized particles. 11 Provided that the increase of SSC intensity represented the uptake of particles in cells, 53 the concentration-dependent increase of SSC by secondary MPs suggested that phototransformation enhanced the cellular uptake of MPs, in contrast to the nearly unchanged SSC intensity for original EMPs (Figure 8a). Due to the close contact of MPs on the cell membrane, the positively charged MPs showed higher cytotoxicity than the negatively charged MPs, 54 which was opposite to the higher cytotoxicity caused by the carbonyl MPs in this study.…”
Section: Characterization Of Zno Nps and Mps Extracted Frommentioning
confidence: 99%
“… 88 However, no harmful effects were found in treated animals when AgNPs were coated with polyethylene pyrrolidone (PVP-AgNPs). 89 Spleen size and weight in Wistar rats increased significantly on the 28th day after intravenous injection of 20 nm and 100 nm silver QDs. 90 The authors suggested that the increase in T, B and NK cell numbers might be the reason for the weight increase of spleen.…”
Section: In Vivo Toxicity Of Qdsmentioning
confidence: 97%